Analysis of Flow Characteristics and Paracetamol Tablet Hardness Using 2D Double Mixer of Design Drum Type with Rotation and Mixing Time Variations - Bambang Setyono; Fahmi Ardianti Purnawiranita (Journal of Mechanical Engineering, Science, and Innovation, 2021)
One of the tablet manufacturing processes using the wet granulation method is the process of mixing the active ingredient granules, fillers, binders and pelicans. The parameters of the mixing process are important to study because they will affect the physical properties of the tablet. This study studied the effect of the variable duration and the size of the mixing cycle on the physical properties of paracetamol tablets using a 2D double mixer. The results of the analysis and testing showed that the variation of mixing time and the size of the rotation had a significant effect on the flow properties of the granules and the hardness of the tablets. In addition, the optimal parameter results to obtain optimal tablet hardness occurred at 15 minutes of mixing process and 50 rpm of rotation.